Effects of age on motor excitability measures from children and adolescents with Tourette syndrome - Pépés, Sophia E.; Draper, Amelia; Jackson, Georgina M.; Jackson, Stephen R. (Elsevier, 2016)
Tourette syndrome (TS) is a neurological disorder characterised by vocal and motor tics. It is associated with cortical–striatal–thalamic–cortical circuit [CSTC] dysfunction and hyper-excitability of cortical motor regions. TS follows a developmental time course, in which tics often become increasingly more controlled during adolescence. Importantly, however, a substantial minority of patients continue to have debilitating tics into adulthood. This indicates that there may be important differences between adult TS patients and children and adolescents with the disorder. We use TMS to examine cortical motor excitability in a sample of children, adolescents and young adults with TS. We demonstrate that, in contrast to studies of adult patients, resting motor threshold and the variability of MEP responses are increased in children with TS, while the gain of motor excitability in reduced. Importantly, we demonstrate that these differences normalise with age over adolescence. We conclude that these effects are likely due to a developmental delay in the maturation of key brain networks in TS, consistent with recent brain imaging studies of structural and functional brain connectivity. Importantly, these findings suggest that the alterations in brain network structure and function associated with TS may be quite different in children and adult patients with the condition.